RISIKO DAN FAKTOR FAKTOR YANG MEMPENGARUHI PRODUKSI GULA AREN CETAK DI DESA BELIMBING, KABUPATEN TABANAN - Wayan - Widyantara (Universitas Udayana, 2019)
ABSTRACT Palm plants (Arrenga pinnata Merr) until now are not widely cultivated, but they are still forest plants. This plant can be used very much, both as a household appliance and as a home industry. The main results that are widely used in home industries are sap which is processed into palm sugar, which is then used as a sweetener in various kinds of cakes, drinks and others. This research was conducted to determine the factors that influence the production of palm sugar and to find out the risks in the small industry of palm sugar. From this study, it is expected to be used as a material consideration in advancing the palm sugar industry in rural areas, especially in the research area. This research was conducted in the Belimbing Village of Tabanan Regency, Bali. The results of this study indicate that only the factor of craftsman experience and the volume of roomie can affect palm sugar production, from five other factors that are suspected. Making palm sugar from sap material has a large risk of production of 115,587 kg, but it is still easily avoidable by craftsmen. With a risk threshold of producing 35.74 kg of printed palm sugar.